Disparity in employment distribution and implementation of federal character policy in the Nigerian civil service - Onimisi, Timothy (2019)
The Nigerian civil service is a colonial creation whose activities were geared towards colonialist interests. Thus, employment distribution in the civil service was lopsidedly structured for that purpose. Regrettably, the lopsidedness and disparity in employment distribution continued even after Nigeria’s independence. Apparently disturbed with the disparity, the Nigerian government enacted the Federal Character Policy (FCP) as captured in Section 153, Sub-section 1c of the constitution of the Federal Republic of Nigeria. The policy was enacted to ensure equality in employment distribution in the country’s civil service. Unfortunately, the implementation of the Federal Character Policy appears to be ineffective because disparity still characterizes employment distribution in the Nigerian civil service. The ineffectiveness in the implementation of the policy has led to the rivalry, call for secession, disharmony, and discontent among the citizens. It is against this backdrop that this study sought to investigate reasons for the ineffective implementation of the Federal Character Policy which was enacted to ensure equal employment distribution in the Nigerian Civil Service. As well as the causes of persistent disparity in the employment distribution in the Nigerian civil service and the strategies that can ensure the implementation of the Federal Character Policy in the Nigerian civil service. A qualitative case study approach was used in this study as it helps to understand a complex social phenomenon and it captures the essential aspect of an issue from the perspective of the study’s core informants. The study adopted purposive sampling in selecting the 24 key informants which were drawn from principal staff of the Employment and Appointment Units of the Federal Civil Service Commission, principal staff from the Monitoring and Enforcement Department of the Federal Character Commission, Academicians (with expertise in public policy), Non-Governmental Organizations (NGOs), Serving Civil Servants (Employed) / Applicants (Unemployed/Grassroots), and Job Search Industries (Recruitment Agencies) to ensure wider representation. Pilot interviews were initially carried out, before an in-depth interview with all the informants. This was followed up with content analysis and analysis of collected data. The research found that disparity continues to ravage the employment distribution in the Nigerian civil service because of political influence, conflict of interest and ethnic bias. Other important findings related to the reasons for the ineffective implementation of the Federal Character Policy in the Nigerian civil service were enforcement challenges, traps in the implementation of the Federal Character Policy, the personal interest of policy implementers and corruption. However, the study found that the implementation of the policy can be achieved through an all-inclusive implementation strategy, the establishment of a Federal Character Tribunal and application of sanctions to policy defaulters. Finally, the study provided valuable insight into the employment distribution disparity in the Nigerian civil service and causes of the ineffective in the implementation of the Federal Character Policy, as well as strategies that will ensure implementation of the policy.